2017
DOI: 10.1097/md.0000000000006844
|View full text |Cite
|
Sign up to set email alerts
|

Application of a buprenorphine transdermal patch for the perioperative analgesia in patients who underwent simple lumbar discectomy

Abstract: This study aimed to investigate the perioperative analgesic effect of a buprenorphine transdermal patch in patients who underwent simple lumbar discectomy.In total, 96 patients were randomly divided into parecoxib intravenous injection (Group A), oral celecoxib (Group B), and buprenorphine transdermal patch groups (Group C). The pain status, degree of satisfaction, adverse effects, and condition in which the patient received tramadol hydrochloride for uncontrolled pain were recorded on the night before surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Surgical procedures included spine surgery, 17 , 19 , 22 major 15 and elective 18 abdominal surgery, hysterectomy and myomectomy, 20 , 21 hip surgery, 16 and hallux valgus 23 corrections. Transdermal buprenorphine was started 6 to 48 hours before surgery in doses ranging from 5 mcg h −1 to 52.5 mcg h −1 15 , 16 , 17 , 18 , 22 , 23 and maintained for 1–7 days after the procedure. Only one study initiated transdermal buprenorphine 36 hours after surgery and maintained it for 28 days after the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical procedures included spine surgery, 17 , 19 , 22 major 15 and elective 18 abdominal surgery, hysterectomy and myomectomy, 20 , 21 hip surgery, 16 and hallux valgus 23 corrections. Transdermal buprenorphine was started 6 to 48 hours before surgery in doses ranging from 5 mcg h −1 to 52.5 mcg h −1 15 , 16 , 17 , 18 , 22 , 23 and maintained for 1–7 days after the procedure. Only one study initiated transdermal buprenorphine 36 hours after surgery and maintained it for 28 days after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“… 17 Control groups received placebo, 18 , 19 , 20 tramadol, 16 , 17 a different dosage of transdermal buprenorphine. 18 , 20 , 21 Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) 22 , 23 or transdermal fentanyl. 15 The risk of bias summary for included studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach avoids oral and intravenous drugs and provides psychological comfort to the patients. 25 Specifically for the patients presenting comorbid conditions and polypharmacy complications, the extended analgesia duration offered by the BTDS allowed less frequent dosing, which may help improve patient acceptability.…”
Section: Discussionmentioning
confidence: 99%